KESADARAN DAN KETAATAN HUKUM MASYARAKAT PEKALONGAN TERHADAP PENOLAKAN DISPENSASI KAWIN - Abadi, Khafid; Septiawan, Bagus; Zahroh, Ulfia (Mitsaqan Ghalizan, 2024)
This research analyzes the legal awareness and compliance of the Pekalongan Regency community in response to the rejection of marriage dispensation by the Religious Court, using Soerjono Soekanto’s theory of legal awareness and Tom R. Tyler’s theory of legal compliance. This study is a field research with a descriptive qualitative approach, focusing on the collection of empirical data from in-depth interviews with individuals whose applications were rejected by the Kajen Religious Court, as well as the analysis of statistical documents related to marriage dispensation cases in the region. The findings reveal that the community’s legal knowledge, particularly regarding the minimum marriage age stipulated by law, is relatively good. However, their understanding of the substantive reasons behind the court’s rejection of marriage dispensation remains low. Public attitudes towards the court’s decision vary; some accept the decision with a positive attitude, while others reject it, feeling that it is unjust. The observed legal behavior patterns also vary, with some community members choosing to postpone marriage in accordance with legal requirements, while others proceed with unregistered marriages (siri) due to social pressure and religious beliefs. Overall, compliance with the law regarding the rejection of marriage dispensation in Pekalongan Regency is not solely based on the threat of sanctions but is also influenced by perceptions of legitimacy, procedural and substantive justice, as well as social and religious influences